The Impact of the Three Pushes Takeoffs Angel’s Phases and Their Distributions Strides Lengths on the Performance in Triple Jump - Zerf, Mohammed (International Journal of Modern Trends in Engineering and Research (IJMTER), 2015)
The purposes of this study were to compare the technique practiced by elite world triple jumper to determine the impact of modality pushes Phrases Takeoffs Angles and the Distributions of Strides Lengths phases allowing the elite to exceed 17-meter, were we have neglect dependence on the practice distribution modality, to explore the weakness in results. From the confirmation of (Hui Liu, 2012) that the weakness or the success of the jumper is in the role of the velocity conversion coefficient affected which technique achieved the longest distance to the assessment of (James G. Hay and John A. Miller, Jr., 1985). That the triple Jump is composed of three take-off phases (Hop, Step, and Jump), each plays an important role, as they require the jumper to tolerate extremely high forces of impact and to maintain a high level of horizontal velocity. Through previous theoretical background, our subjects were The Results of world elite 2009. In the lack of new technology, Modern measuring instruments kinematics or kinetics. Our study based on rapports take-off angels as measure and Stride length Jump distance of world elite 2009 from the (Project by the German Atletecs Federration, 2009) To verify the hypothesis that support: The factors affecting the performance are due, to the confirmation of (Gordon Robertson & all, 2004) that any less change in the step phase change the angular momentum created by hop phase and the Effort distribution decides jumping techniques in different phases especially in the hop and step phases set by (Hay, 1992).
Keywords: Three Pushes Takeoffs Angel’s Phases; Stride Length; Performance Triple Jump